Microencapsulation to Maintain the Activity and Stability of Drug Substances: A Review: Activity, Stability, Coacervation, Microencapsulation, Spray Drying, Solvent Evaporation - Almadanti, Sintia Ayu; Makmur, Indra; Asra, Ridho; Umar, Salman (Asian Journal of Pharmaceutical Research and Development, 2020)
Purpose: The microencapsulation method is one of the most widely used techniques to protect bioactive compounds from various environmental factors such as evaporation, oxidation, degradation of temperature, humidity, and light. Therefore, it can extend product shelf life and avoid damage so that it can last a long time and can still be utilized by the body well1. Selection of Data Sources: In compiling a review, this article used a literature study by finding sources or literature in the form of national and international journals in the last 10 years (2010-2020). Data search was also carried out using online media with the keywords as follows: microencapsulation, microcapsules, and microencapsulation methods. The search for the main references used in this review article was conducted through trusted websites such as Science Direct, Pubmed, Google Scholar, and other published and trustworthy journals. Conclusion: Based on the results of several studies, it can be concluded that microencapsulation using several of the above methods can provide protection for the substance / drug against environmental influences, and it can maintain the stability of a substance / drug so that it can extend the drug release time.